Wage cyclicalities and labor market dynamics at the establishment level: theory and evidence - Merkl, Christian; Stüber, Heiko (Bonn, 2017)
"Using the new AWFP dataset that covers all German establishments, we document a substantial cross-sectional heterogeneity of establishments' average real wages over the business cycle. While the median establishments' real wages are procyclical, there is a large fraction of establishments with countercyclical real wages. We are the first to show that establishments with more procyclical wages have a less procyclical hires rate and employment behavior. We propose a labor market flow model that is able to replicate these facts and thereby allows us to run counterfactual exercises. When we set the wage cyclicalities of all establishments to the one of the most procyclical establishments, labor market volatilities drop by more than 50 percent."